Pasifika diaspora connectivity and continuity with Pacific homelands: Material culture and spatial behaviour in Brisbane - Faleolo, Ruth (Lute) (The Australian journal of anthropology, 2020)
This paper presents an interesting discussion and analysis of Pasifika (specifically Tongan and Samoan) migrants in Brisbane, and the diverse adaptive cultural practices they use to promote a sense of wellbeing and cultural continuity in diaspora contexts. Pacific Island migrant perspectives of wellbeing and worldviews are linked to their spatial behaviour and material cultural adaptations within places like Brisbane. The characteristics of the Brisbane urban landscape create the material cultural adaptations that have been observed in diaspora contexts, including places of dwelling, community and church gatherings. They are commonly displayed during family or community events, in both private and public spaces. In order to understand the significance of material cultural adaptations we must also consider the underpinnings of the materials and templates used within context. Preliminary qualitative findings have been drawn from a wider-scale research project that has explored Pasifika migrants (of Samoan and Tongan descent) perceptions and experiences of wellbeing during 2015‒2018. This inquiry has rendered significant evidence of cultural values and identity elements originating from Samoa and Tonga and retained by generations of Brisbane-based Pacific Islanders, through adapted material culture and shared spatial behaviour.